Sinus arrest in a p.Arg160X-DSP-positive patient without evidence of desmoplakin-mediated cardiomyopathy: a case report - Tan, Nicholas Y.; Giudicessi, John R.; Harvey, Jason R.; Asirvatham, Samuel J.; Siontis, Konstantinos C. (Frontiers in Cardiovascular Medicine, 2023)
Background Pathogenic/likely pathogenic variants in DSP-encoded desmoplakin are strongly associated with arrhythmogenic cardiomyopathy (ACM). However, their contribution towards sinus node dysfunction has not been well-delineated. Case Summary A 74-year-old man with a pathogenic variant of DSP-encoded desmoplakin (c.478C >T; p.Arg160X) but no evidence of ACM presented with one episode of syncope in the setting of a gastrointestinal illness. Workup including echocardiography, cardiac magnetic resonance imaging, and Holter monitor did not show evidence of ACM or significant arrhythmias. One month later, he experienced several closely-spaced episodes of syncope associated with long sinus pauses and sinus arrest documented on telemetry. He underwent urgent dual chamber pacemaker implantation, during which a ventricular programmed stimulation study was performed and was negative for sustained ventricular arrhythmias. His syncopal episodes resolved and he had no recurrent events on three-month follow-up. Discussion As highlighted here, DSP-encoded desmoplakin pathogenic/likely pathogenic variants may contribute to isolated sinus node dysfunction. This clinical link should be further explored in larger studies involving patients with DSP variants.